Loop Mediated Isothermal Amplification: Principles and Applications in Plant Virology - Stefano Panno; Slavica Matić; Antonio Tiberini; Andrea Giovanni Caruso; Patrizia Bella; Livio Torta; Raffaele Stassi; Salvatore Davino (Plants, 2020)
In the last decades, the evolution of molecular diagnosis methods has generated different advanced tools, like loop-mediated isothermal amplification (LAMP). Currently, it is a well-established technique, applied in different fields, such as the medicine, agriculture, and food industries, owing to its simplicity, specificity, rapidity, and low-cost efforts. LAMP is a nucleic acid amplification under isothermal conditions, which is highly compatible with point-of-care (POC) analysis and has the potential to improve the diagnosis in plant protection. The great advantages of LAMP have led to several upgrades in order to implement the technique. In this review, the authors provide an overview reporting in detail the different LAMP steps, focusing on designing and main characteristics of the primer set, different methods of result visualization, evolution and different application fields, reporting in detail LAMP application in plant virology, and the main advantages of the use of this technique.